2012
DOI: 10.1242/jeb.068791
|View full text |Cite
|
Sign up to set email alerts
|

In ovotemperature manipulation differentially influences limb musculoskeletal development in two lines of chick embryos selected for divergent growth rates

Abstract: SUMMARYSelective breeding has led to diverging phenotypic evolution in layer and broiler chickens through genomic and epigenetic modifications. Here we show that in ovo environmental manipulation differentially influences embryonic limb muscle phenotype in these two breeds. We demonstrate that raising incubation temperature from 37.5 to 38.5°C between embryonic days (ED) 4 and 7 increased motility and body mass in both layer and broiler embryos. In layers, this was accompanied by gastrocnemius muscle hypertrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 62 publications
0
18
0
Order By: Relevance
“…2011; Al-Musawi et al. 2012). Such conversions of satellite cells from a myogenic to adipogenic lineage may also contribute to increased intramuscular fat depots that negatively impact treatment in individuals with diabetes mellitus (Hilton et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2011; Al-Musawi et al. 2012). Such conversions of satellite cells from a myogenic to adipogenic lineage may also contribute to increased intramuscular fat depots that negatively impact treatment in individuals with diabetes mellitus (Hilton et al.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is supported by Al-Musawi et al. (2012) who showed increased intramuscular fat deposition in the gastrocnemius muscle of 18-day-old chicks incubated for 3 days at one degree above normal in ovo incubation temperature. Taken together, the results from the present study support the conversion of myogenic satellite cells to an adipogenic pathway due to thermal manipulation.…”
Section: Discussionmentioning
confidence: 99%
“…Al-Musawi et al (2012) showed that higher egg incubation temperature alters expression of myogenic growth factors and increases muscle size in broiler chickens. While studies such as these reveal the importance of the genotypeenvironment interaction in early developmental programming, it is not as clear how phenotype is changed when exposures occur during later postnatal development.…”
mentioning
confidence: 99%
“…The incubation temperature design are listed in Figure 1. We divided the incubation stages into three phases, early embryonic stages (ED1–10), middle embryonic stages (ED10–20), later embryonic stages (ED20–27), which based on previous studies in birds (Collin et al., 2007; Hammond et al., 2007; Al-Musawi et al., 2012). Six ducklings were slaughtered by rapid bloodletting at ED10, 20 and 27.…”
Section: Methodsmentioning
confidence: 99%